Letter writing as a social practice - Barton, David, 1949-; Hall, Nigel, 1947- (Studies in written language and literacy, 2000)
This book explores the social significance of letter writing. Letter writing is one of the most pervasive literate activities in human societies, crossing formal and informal contexts. Letters are a common text type, appearing in a wide variety of forms in most domains of life. More broadly, the importance of letter writing can be seen in that the phenomenon has been widespread historically, being one of earliest forms of writing, and a wide range of contemporary genres have their roots in letters. The writing of a letter is embedded in a particular social situation, and like all other types o.